How do you answer a 65-year-old, without a history of cardiac or vascular disease, when they ask, "Can I participate in competitive sports?" - Gianturco, L.; Gianturco, V. (Cardiology Practice, 2021)
Nowadays, life expectancy is growing, and subjects aged >65 may often be considered "younger" than their chronological age. Therefore, we see quite a large number in this population routinely practising physical activities (PA) and not simply for their leisure-time. This is useful as a contrast to sedentary lifestyles and provides psycho-social benefits. However, it is increasingly pivotal to screen these subjects by a comprehensive pre-competition assessment; This is especially true concerning their cardiovascular (CV) system, not least because very often pre-competition exams might reveal important and previously unknown heart abnormalities (asymptomatic and/or paucisymptomatic conditions).